Digital literacy and strategic (dis)engagement: examining how functional and critical digital literacy shapes participation - Polizzi, Gianfranco (Information, communication & society, 2025)
Employing semi-structured interviews enhanced by think aloud and diary methods, this article explores how digital experts (e.g., information/IT/media professionals) and civic advocates (e.g., political party candidates, activists) deploy digital literacy to participate in society. These groups - who are digitally savvy and civically active, respectively - are ideal for exploring the intersection of digital literacy and participation in public, community, and/or political life. This study found that their practices (e.g., reading news, sharing political content, campaigning) are informed by a wealth of functional and critical digital skills and knowledge. These enable them to strategically overcome bias, misinformation, and their own privacy concerns, and to navigate both the potentials and limitations of the internet in line with different ideologies. Their practices, furthermore, often involve what this article refers to as strategic disengagement (i.e., the deliberate withdrawal from engaging with online content and/or platforms). This article shows how functional and critical dimensions of digital literacy can be deployed in tandem to make strategic decisions to participate. In doing so, it problematises the assumption that critical digital literacy is inherently progressive and that online disengagement results necessarily from poor functional digital literacy. The implications of these findings for research and practice are discussed.